Bang Jago Frozen Food / Mohammad Ammar Afifi Daud ... [et al.] - Daud, Mohammad Ammar Afifi; Romainoor, Muhammad Firdaus; Roslee, Muhammad Sairizan; Nor Azli, Nur Hazirul Aiman; Abd Jalil, Syafiq (2021)
Bang Jago Frozen Food is a partnership business. This business plan is mainly prepared for entrepreneurs, investors, bankers, financial assistant providers, suppliers, customers and employees. This company is owned by Mohammad Ammar Afifi bin Mohd Daud and located at 13G, Jalan Anggerik Vanila X31/X, Kota Kemuning, 40460 Shah Alam, Selangor. We name our company as Bang Jago Frozen Food because it symbolizes all of our customers and professional and educated staff. By having a good company name, it gives a good impression and helps to open customers' eyes so that they will be attracted to our company. We name our company as Bang Jago Frozen Food because it symbolizes all of our customers and professional and educated staff. By having a good company name, it gives a good impression and helps to open customers' eyes so that they will be attracted to our company.